Silvernanoparticle‐induced hemolysis confounded with direct antiglobulin test‐negative autoimmune hemolytic anemias diagnosis. Issue 12 (3rd November 2022) - Ringel, Frauke; Kiesewetter, Holger; Mayer, Beate; Bartolmäs, Thilo; Sehouli, Jalid; Salama, Abdulgabar
Abstract: Background: We describe here the first patient with recurrent hemolysis related to disinfectant containing silver nanoparticles (AgNps). Methods: A 58‐year‐old chemist repeatedly experienced DAT‐negative (Coombs‐negative) hemolysis during the last 5 years. He was treated with a number of immunosuppressive drugs including 18 times rituximab. The attempt to treat him with cyclosporine A served only to increase the rate of hemolysis. Only by chance, we revealed that the patient regularly used a hand disinfectant containing AgNps. Serological testing was performed using standard techniques. Eryptosis was measured by binding annexin to exposed phosphatidylserine (PS) of the circulating red blood cells (RBCs). Results: Antiglobulin tests remained negative, and PS exposing RBCs were detected two times during the last hemolytic episodes. Hemolysis completely disappeared following discontinuation of AgNp containing products. Conclusion: AgNps are increasingly being used in a large variety of products. Recently, it was reported that they induce in vitro prohemolytic and procoagulant effects via oxidative stress and eryptosis. The clinical findings imply the hemolysis was provoked by the patient's regular use of cleansing products containing AgNps. Our finding might help to explain the etiology of hemolytical disorders that may remain obscure in many cases.